การประมาณค่าอัตรามรณะของผู้สูงอายุไทยโดยใช้วิธีการโฮริอูจิกับโคล และวิธีการมิทรา - ปาณิสรา แย้มสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The objective of this research is to calculate pension premiums. The first part is to estimate the mortality rate of the Thai elderly with six mortality models, including Gompertz model, Kannisto model, Gompertz model by Horiuchi-Coale parameter estimation method, Gompertz model by Mitra parameter estimation method, Kannisto model by Horiuchi-Coale parameter estimation method, and Kannisto model by Mitra parameter estimation method. This study employed two datasets: one from the Ministry of Interior containing the number of populations by age and sex from 2015–2021 and another from the Ministry of Public Health containing the number of deaths by age and sex from 2016–2020. The obtained mortality rates were compared to determine the most suitable model using the MAPE. After that, calculate the net premiums of the designed pension product and to compare with the net premiums computed from the 2009 Thai Pension Table.Premiums of a pension contract with a ten-year annual premium payment period, covering individuals aged 30 to 50 and providing coverage until the age of 110 with a 2% annual interest rate. The premium increased with the age of the insured. Premiums for men were lower than for women aged 30 to 36, but higher for ages 37 to 50. The premium was lower than that using the 2009 Thai pension table, and the mortality rates were not affected by the COVID-19 outbreak.